Comparative in vitro evaluation of fungicides, botanicals and bioagents for suppressing Alternaria alternata causing Alternaria leaf spot in ber - Abdul Ahad; H. K. Singh; Jitendra Kumar; Shubham Patel; Vivek Singh; Divya Singh; Manish Kumar Maurya (The Bioscan, 2025)
The present experiment was conducted during 2024-25 in the laboratory of the Department of Fruit Science, College of Horticulture and Forestry, Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya, to evaluate the efficacy of eleven chemical fungicides at four concentrations (750 ppm, 1000 ppm, 1500 ppm, and 2000 ppm), along with ten botanical extracts and two bio-agents tested at three concentrations (10%, 15%, and 20%) against Alternaria alternata. The study was carried out using poisoned food technique for chemical fungicides, botanical extracts and bio-agent with Completely Randomized Design (CRD), Among the fungicides Hexaconazole and Tebuconazole proved to be the most effective chemical fungicide recording complete growth inhibition (100%) at all the four tested concentrations which was followed by Fluxapyroxad 6.25% + Epoxiconazole 6.25% EC (100%) at 1500ppm and 2000ppm, Kasugamycin 5% + Copper oxychloride 45% WP (7.90mm, 91.22%) followed by Thiophanate methyl 38% + Kasugamycin 2.21% SC (8.13mm, 90.97%) at 2000ppm whereas, at 750ppm Copper oxychloride (38.40mm) was least effective in reducing fungal growth (57.33%). Among the botanical extracts and bioagents, recording average highest growth inhibition observed in Garlic bulb extract (80.59%) followed by Eucalyptus (76.11%), Trichoderma viride (72.95%) and minimum inhibition percent (31.30%) was observed in Ashok. The study indicated better performance of some chemical fungicides even at lower concentrations i.e. 750ppm and 1000ppm also. So, such effective fungicides could be used to minimize hazardous effect. Significant effect of some botanical extracts and bio-agent against pathogen growth suggests their application as potential control agent alternative to chemicals.